Double-headed small-bowel capsule endoscopy: Real-world experience from a multi-centre British study. Issue 4 (April 2021) - Yung, DE; Robertson, AR; Davie, M; Sidhu, R; McAlindon, M; Rahman, I; Patel, P; Sinha, L; Mason, S; Brzeszczynska, J; Douglas, S; Plevris, JN; et al.
Abstract: Introduction: Capsule endoscopy (CE) is well established the investigation of small-bowel (SB) pathology. We compared the use of double-headed (DH) capsules, to conventional single-headed (SH), in a real-world patient cohort in the first multicentre British study. Methods: Over 9 months, patients referred for routine SBCE at 4 tertiary referral centres in the UK underwent DH CE instead of conventional SH using MiroCam Ⓡ MC2000 as per local protocols. One head (L/R) was chosen at random and reported by an expert reviewer. The DH recordings, anonymised and randomised, reported by another expert or re-read after a 4-week interval. For each CE, numbers and types of findings and overall conclusion/diagnosis were compared between SH and DH examinations. Results: 211 CEs were performed. 7 failed to reach the SB; 204 analysed. Indications were: SB bleeding ( n  = 94); ?SB inflammation or reassessment of known inflammatory bowel disease (IBD) ( n  = 84); ?SB neoplasia including suspicious radiological imaging ( n  = 15); and, others e.g. ?celiac disease ( n  = 11). For SB bleeding: 27/94 (28.7%) examinations reported differences between SH and DH readings. In 17 (18.1%) the findings were clinically significant. SH CE missed angiectasias (5 pts), SB inflammation (7 pts), oesophagitis (2 pts) and SB masses (2 pts). In 1 patient, the extent of angiectasias seen was greater on the DH reading. For IBD: findings differed in 30/84 (35.7%) of CEs; 11 (13.1%) were clinically significant. In 5, signs of active inflammation were missed by the SH reading. In 6, assessment of extent/severity differed. For?SB neoplasia findings differed in 2/15 (13.3%) of examinations. Both were clinically significant. For others: 1/11 (9.1%) examinations differed; however, not deemed clinically significant. Overall, use of DH CE impacted the diagnosis in 30/204 (14.7%). Conclusions: The use of DH CE provides more information with the potential to change clinical diagnosis and therefore management. Therefore, the routine adoption of DH CE in SB assessment should be considered.